Numerical Methods for 3D Tokamak Simulations Using a Flux‐Surface Independent Grid. Issue 4 (June 2014) - Stegmeir, A.; Coster, D.; Maj, O.; Lackner, K.
Abstract A numerical approach for 3D Tokamak simulations using a flux surface independent grid is presented. The grid consists of few poloidal planes with a Cartesian isotropic grid within each poloidal plane. Perpendicular operators can be discretised within a poloidal plane using standard second order finite difference methods. The discretisation of parallel operators is achieved with a field line following map and an interpolation. The application of the support operator method to the parallel diffusion operator conserves the self‐adjointness of the operator on the discrete level and keeps the numerical decay rate at a low level. The developed numerical methods can be applied to geometries where an X‐point is present. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)